2016
DOI: 10.1177/0897190015585876
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in CYP2R1 and GC Genes Associated With Vitamin D Deficiency Status

Abstract: This cross-sectional study enrolled 180 patients at a private family practice in Virginia. Total serum vitamin D concentrations were obtained weekly from January 30, 2013, through March 30, 2013, in consecutive patients regularly scheduled for laboratory work at the practice. Patients were categorized into 2 groups and analyzed for variant alleles in vitamin D receptor ( VDR; rs2228570), cytochrome P450 2R1 ( CYP2R1; rs10741657), 7-dehydrocholesterol reductase ( DHCR7; rs12785878), and group-specific component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
5
39
0
Order By: Relevance
“…In this study, we also found that SNP CYP2R1 rs10741657 is associated with both insufficiency and deficiency of 25OHD, which is consistent with other studies. 7 , 19 , 20 On the other hand, Li et al, 13 did not find any association between SNP CYP2R1 rs10741657 and vitamin D level, while Elkum et al, 17 found that it was positively associated with vitamin D level among South Asian population, but not among Arabs population. We also studied the effect of SNP CYP2R1 rs1993116, and we found that it was not associated with variability in vitamin D, consistent with the finding reported by Li et al, 13 and different from the finding reported by Robien et al, 19 although both studies were carried out on Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that SNP CYP2R1 rs10741657 is associated with both insufficiency and deficiency of 25OHD, which is consistent with other studies. 7 , 19 , 20 On the other hand, Li et al, 13 did not find any association between SNP CYP2R1 rs10741657 and vitamin D level, while Elkum et al, 17 found that it was positively associated with vitamin D level among South Asian population, but not among Arabs population. We also studied the effect of SNP CYP2R1 rs1993116, and we found that it was not associated with variability in vitamin D, consistent with the finding reported by Li et al, 13 and different from the finding reported by Robien et al, 19 although both studies were carried out on Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Slater, N.A. et al [13] showed that non-carriers of rs10741657 risk alleles (CG) had higher levels of 25(OH)D. Ramos-Lopez et al [12] found a significant association between the genotype of rs10741657 and serum 25(OH)D concentrations in 203 German diabetic patients. Two genome-wide association studies (GWAS) on genetic determinants of serum of vitamin D published in 2010 [14,15] and found that rs10741657 was significantly associated with 25(OH)D concentrations in 30,000 subjects of European descent from 15 cohorts or in 496 unrelated healthy Caucasian subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This stage of the VD metabolic pathway is one of those in which researchers have searched for variants influencing MS, especially in CYP27B1 ; it is therefore surprising that no association was found. Associations have been described between VD deficiency and numerous genetic variants (Lafi, Irshaid, El‐Khateeb, Ajlouni, & Hyassat, ; Li et al, ; Lu et al, ; Nissen et al, ; Signorello et al, ; Slater, Rager, Havrda, & Harralson, ; Wang et al, ; Zhang et al, ) (Table S1). However, these associations do not necessarily represent increased risk of MS, as no correlation has been demonstrated between the disease and plasma VD level (Ahn et al, ).…”
Section: Discussionmentioning
confidence: 99%